Implementation of Cooperative Learning Model Three Stay Two Stray Assisted by ARaRaT to Reduce Students' Misconceptions on Fluid Dynamic Material - Evelyna Gressianita; Achmad Samsudin; Agus Danawan (Berkala Ilmiah Pendidikan Fisika, 2024)
This research aims to identify a decrease in students' misconceptions about dynamic fluid material after learning is implemented Three Stay Two Stray (TSTS) with the help of ARaRaT in experimental and learning classes and TSTS in the control class. This research uses mixed methods with a research design embedded in an experimental design. The research sample involved 65 students (22 male and 43 female) in class XI MIPA at one of the public high schools in Cimahi City. The technique for collecting data on students' misconceptions used the test instrument Four-Tier Fluid Dynamic Concept (FT-FDC), which consists of 10 questions that are analyzed using the reducing quantity misconceptions equation to see the decrease in the number of students' misconceptions after being given treatment. The results of the data analysis in the experimental class showed a change in the percentage of students experiencing misconceptions from 38.8% to 10%, with an average decrease of 28.8%. Meanwhile, the percentage change in the number of students' misconceptions in the control class was obtained from 36.1% to 23.9%, with an average percentage decrease of 12.2%. This research implies that students become more skilful in conducting experiments with the help of ARaRaT and better understand concepts that are not only in the form of verbal statements but with various forms of representation of images, graphs, tables, mathematical equations, and even 3D media with the help of Augmented Reality. Thus, implementing TSTS learning assisted by ARaRaT can be an alternative to physics learning to reduce students' misconceptions.